ダイ36ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1995-1996 - 召田, 成美; メシダ, シゲミ; Meshida, Shigemi (1997)
P(論文) 第36次南極地域観測越冬隊40名(昭和基地越冬31名, ドームふじ観測拠点越冬9名)は, 1994年11月14日東京港を出港し, 1996年3月27日成田に帰着した。この間, 第105回南極地域観測統合推進本部総会において審議承認された「第36次南極地域観測隊行動実施計画」に則って観測活動を行い, すべての任務を無事完了した。昭和基地では1995年2月1日から翌年1月31日の間, ドームふじ観測拠点では同年1月29日から翌年1月23日の間, 第36次隊による基地の維持運営を行った。「しらせ」が2年ぶりに昭和基地に接岸し, 夏期オペレーションが予定どおり行われたこともあって, 越冬は最初から最後まで極めて順調に経過した。昭和基地では第35次隊より引き継いだ定常観測・研究観測のほか, 夏期間に設置した大型短波レーダーを用いて「磁気圏ダイナミックスの観測」を開始した。またラングホブデぬるめ池においては, 南極半島にしか生息しないと言われていた種子植物が新たに発見された。設営関係では建築担当隊員が初めて越冬し, 各棟の外扉の交換などを中心に老朽化した基地建物の修理・整備を行った。さらにドームふじ観測拠点において越冬観測が開始されたため, 昭和基地においてもそのサポートが重要な任務のひとつとなった。ドームふじ観測拠点においては, 「氷床ドーム深層掘削観測計画(5年計画の4年次)」に基づき越冬観測を開始したが, 初越冬のため観測業務以外の各種施設の建設・整備も大きな比重を占めた。氷床深層掘削は諸準備ののち8月下旬より本格的に開始され, 難航したが12月22日には深度500mを突破し, 最終的には600mを掘削して第37次隊に引き継いだ。 The wintering party of the 36th Japanese Antarctic Research Expedition (JARE-36) executed its planned activities at Syowa and Dome Fuji Stations from 1995 to 1996. The wintering party at Syowa Station, consisting of 31 personnel, carried out its observations and logistic work from February 1,1995 to January 31,1996. Routine and some specific observations for studies of upper atmosphere physics, meteorology, solid earth geophysics, biology and medical science were performed without any serious problems for a full year. Continuous observation of the magnetosphere had started using an HF radar system constructed during the austral summer of 1994/95. A seed plant was discovered near Nurume Lake, Langhovde. It was the first report of a seed plant growing in continental Antarctica. An architect took part in the wintering party for the first time and maintained decrepit buildings. Support work for the wintering party at Dome Fuji Station was one of the principal tasks at Syowa Station. A trip to the Dome Fuji Station was carried out to transport supplies and fuel in the austral spring of 1995. The first wintering activities at Dome Fuji Station started from January 29,1995. The wintering party, consisting of 9 personnel, carried out meteorological and glaciological observations together with deep ...